Blogging as a Means of Professional Development for ELT Professionals - Yadav, Praveen Kumar (Journal of NELTA, 2012)
Reading and publishing articles in journals and organizing conferences, seminars and trainings are common traditional modes of professional development. For journals, they are selective in nature and restricted by money and its turn out is very slow as well. Likewise, physical space and time along with a lot of people are required to get together to organize conferences, seminars and trainings. Furthermore, such traditional modes of developing professionalism in ELT are limited in the scope, not easily accessible resources and they do not provide autonomy to the individuals. But blogging is one of the emerging professional development tools for ELT Professionals. The innovative tool is easily accessible and affordable as it is neither limited in scope nor restricted by money. The present article draws some ideas about how blogging can help, enhance and enrich English Language Teachers and Learners to develop themselves as ELT Professionals. DOI: http://dx.doi.org/10.3126/nelta.v16i1-2.6136 NELTA 2011; 16(1-2): 123-132